RISK-BASED PROCESSES FOR ENSURING THE SECURITY OF CRITICAL INFRASTRUCTURE FACILITIES - Tarasenko, Yu. S.; Savchenko, Iu. V. (Systems and Technologies, 2023)
The article presents a review of research on decision-making from the perspective of risk-information security of a set of critical infrastructure facilities. In the context of increased intensity of regional and sectoral information wars, their steady expansion and impact, primarily on significant areas of modern society, the trend of unscrupulous confrontation of the latest information technologies, which reach cyber espionage, cybercrime and cyberterrorism with the use of information weapons aimed at breaking the security of existing critical infrastructure facilities, is becoming increasingly acute. The meaning of information security is the impossibility of harming the normal functioning and properties of these objects or their structural components. The article builds a structural and linguistic scheme for supporting decision-making from the standpoint of risk-information security of a set of critical infrastructure facilities. As an evaluative positive example, a specific method of implementing the physical security of a set of critical infrastructure facilities is evidently presented. The author analyses the methodological construction of the structural and linguistic scheme for selecting means of protection of a set of critical infrastructure facilities from the perspective of risk reduction. It is shown that it has a universal structure and can actually be used in any organised sphere of society, regardless of the type of industry, size of the organisation, allocated material resources and intellectual level of the staff responsible for this area of security and protection. The author substantiates a part of the structural and linguistic scheme from the standpoint of risk-oriented processes of ensuring the security of critical infrastructure facilities, which reflects: organisational and physical means of protection of general application; specific means of protection of an information system; means of protection in accordance with the problems (against loss of confidentiality, integrity, availability, observability, authenticity and reliability) and threats within the framework of ensuring their security. Using the example of detecting unauthorised aerial attacks by intruders using drones, the article demonstrates the feasibility and possibility of detecting a potential attack by an intruder or intruder using drones using radio physical systems as environmental measurement tools in the form of a circuitry implementation of correlation radar devices of close interaction using a noise-like continuous ultra-high frequency sensing signal with amplitude modulation. It is shown that the optimal choice of the sensing signal, on the one hand, depends on the result of an a priori analysis of the signal function of a particular sensing bundle and its corresponding uncertainty volume, and on the other hand, ensures the concealment of the process of detecting high-resolution drones directly by two parameters – its range and speed.